The influence of prompt on group oral tests. (April 2014) - Leaper, David A.; Riazi, Mehdi
This paper reports an investigation into how the prompt may influence the discourse of group oral tests. The group oral test, in which three or four participants are rated on their ability to discuss a prompt, is a format for assessing the spoken ability of language learners. In this study, 141 Japanese university students were videoed in 41 group orals of three or four test-takers. Although the four different prompts written for the test were supposed to be of equal difficulty, they were found to be substantially different in the type and number of questions that comprised them. Analysis of the transcribed interactions revealed significant differences in turns taken, syntactic complexity and fluency of the interactions they elicited. A qualitative examination revealed that the two prompts that elicited longer, more complex turns did so by encouraging test-takers to explain their family circumstances or speculate about their future. Prompts with more factual content elicited shorter, less complex turns and the prompt that test-takers responded to with the least fluency required the test-takers to talk about a more personal subject. The implications for rating and creating prompts are discussed, and the need to tailor them to the purpose of the test.